Liquid crystal resin composition for fans and fan using same
Patent Information
- Application Number
- JP2021017613
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-05
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-02-05
AI Technical Summary
【0016】 本発明によれば、振動減衰特性及びねじれ剛性に優れ、ノイズが抑制されたファンを与えるファン用液晶性樹脂組成物、前記組成物からなるファンを提供することができる。
Smart Images

Figure 0007644612000005 
Figure 0007644612000006 
Figure 0007644612000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a liquid crystalline resin composition for a fan and a fan using the same. [Background technology]
[0002] Liquid crystalline resins, such as liquid crystalline polyester resins, have a good balance of excellent heat resistance, chemical resistance, electrical properties, etc., and also have excellent dimensional stability, and therefore are widely used as high-performance engineering plastics.
[0003] Fans are used to cool electronic devices by forcing convection of fluids such as air (for example, see Patent Document 1). A fan is usually composed of a fan impeller that has multiple blades and generates a fluid flow by rotating, a motor that rotates the fan impeller, a housing that contains the fan impeller and the motor, etc. Conventionally, polyamide, polybutylene terephthalate, etc. have been used as resins for the fan impeller and the housing. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2005-039253 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, with the launch of 5th generation mobile communication system (5G) services that enable ultra-high speed, ultra-low latency, and multiple simultaneous connections, the heat generated by electronic devices is increasing due to their high functionality and high speed, making cooling systems increasingly important. There is also a demand for more efficient cooling capacity in cooling fans, and various countermeasures being considered include reducing the thickness of the fan impeller blades (thinning) to increase the number of blades, and rotating the fan faster than before.
[0006] However, when conventional resins are used for fans, thinning the blades can result in problems such as poor molding due to the low fluidity of the resin composition, and noise caused by vibrations can be generated when the fan is rotated at high speeds.
[0007] Therefore, the present inventors have investigated the use of liquid crystalline resins with excellent flowability, but have not found any liquid crystalline resins with excellent vibration damping properties. In addition, liquid crystalline resins generally exhibit high strength in the flow direction, but have a problem in that they are poor in strength in the twisting direction.
[0008] The present invention has been made in consideration of the above circumstances, and has an object to provide a liquid crystalline resin composition for fans which provides a fan with excellent vibration damping properties and torsional rigidity and reduced noise, and a fan made of said composition. [Means for solving the problem]
[0009] The present inventors have found that the use of a liquid crystal resin containing a specific amount of a specific structural unit results in particularly excellent vibration damping properties. They have also found that the above-mentioned problems can be solved by a liquid crystal resin composition that combines the above-mentioned liquid crystal resin with a specific amount of a plate-like filler having a specific aspect ratio, and that has a loss factor within a specific range measured at a specific temperature and frequency. Specifically, the present invention provides the following.
[0010] (1) A liquid crystalline resin composition for a fan, comprising (A) a liquid crystalline resin and (B) a plate-like filler, The (A) liquid crystalline resin contains the following structural units (I), (III), (IV) and (V), and may or may not contain the following structural unit (II), The content of the structural unit (I) relative to all structural units is 35 to 75 mol %, The content of the structural unit (II) relative to all structural units is 0 to 8 mol %, The content of the structural unit (III) relative to all structural units is 4.5 to 30.5 mol %, The content of the structural unit (IV) relative to all structural units is 2 to 8 mol %, The content of the structural unit (V) relative to all structural units is 12.5 to 32.5 mol %, a wholly aromatic polyester which exhibits optical anisotropy when melted, in which the total content of the structural units (I) to (V) is 100 mol % relative to all structural units; The (B) plate-like filler has an aspect ratio, which is the ratio of the average particle size (μm) to the average thickness (μm), of 10 or more, The content of the plate-like filler (B) is 5 to 40% by mass based on the entire liquid crystal resin composition, A liquid crystalline resin composition having a loss factor of 0.05 or more at a temperature of 23°C and a frequency of 10,000 Hz, as measured in accordance with JIS G0602. [ka]
[0011] (2) The (A) liquid crystalline resin comprises structural units (I), (II), (III), (IV) and (V), The content of the structural unit (I) relative to all structural units is 35 to 75 mol %, The content of the structural unit (II) is 2 to 8 mol% based on all structural units, The content of the structural unit (III) relative to all structural units is 4.5 to 30.5 mol %, The content of the structural unit (IV) relative to all structural units is 2 to 8 mol %, The content of the structural unit (V) relative to all structural units is 12.5 to 32.5 mol %, a wholly aromatic polyester which exhibits optical anisotropy when melted, in which the total content of the structural units (I) to (V) is 100 mol % relative to all structural units; The liquid crystal resin composition according to (1), wherein the plate-like filler (B) is glass flakes.
[0012] (3) The liquid crystalline resin composition according to (1) or (2), further comprising (C) a fibrous filler.
[0013] (4) The liquid crystalline resin composition according to (3), wherein the content of the fibrous filler (C) is 5 to 20% by mass based on the entire liquid crystalline resin composition.
[0014] (5) The liquid crystalline resin composition according to (3) or (4), wherein the (C) fibrous filler is glass fiber and / or carbon fiber.
[0015] (6) A fan made of the liquid crystal resin composition according to any one of (1) to (5). Effect of the Invention
[0016] According to the present invention, it is possible to provide a liquid crystalline resin composition for fans which provides a fan having excellent vibration damping properties and torsional rigidity and suppressed noise, and a fan made of said composition. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a perspective view showing a schematic diagram of an axial flow fan among embodiments of fans according to the present invention. [Diagram 2] FIG. 1 is a perspective view showing a schematic diagram of a centrifugal fan according to an embodiment of the present invention. [Diagram 3] 1A and 1B are a front view and a side view of a fan impeller of a centrifugal fan created in an embodiment. [Figure 4] FIG. 4 is a diagram showing a method for measuring a vertical load on a blade in an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described in detail.
[0019] <Liquid crystal resin composition for fans> The liquid crystal resin composition for fans according to the present invention contains a specific liquid crystal resin and a predetermined amount of a plate-like filler having a predetermined aspect ratio, and has a loss factor of 0.05 or more. The liquid crystal resin composition according to the present invention has a loss factor of 0.05 or more, and therefore can provide a fan with excellent vibration damping characteristics and suppressed noise. The loss factor is preferably 0.055 or more, more preferably 0.06 or more. The upper limit of the loss factor is not particularly limited, and may be, for example, 0.08.
[0020] In this specification, the loss factor is a value measured at a temperature of 23° C. and a frequency of 10,000 Hz in accordance with JIS G0602.
[0021] [(A) Liquid crystal resin] The liquid crystal resin composition according to the present invention contains a liquid crystal resin which is the wholly aromatic polyester. The wholly aromatic polyester has particularly excellent fluidity and vibration damping properties, and therefore can be used to favorably mold a fan having excellent vibration damping properties and reduced noise. The liquid crystal resin can be used alone or in combination of two or more kinds.
[0022] The wholly aromatic polyester in the present invention contains the following structural unit (I), structural unit (III), structural unit (IV) and structural unit (V), and may or may not contain the following structural unit (II).
[0023] [ka]
[0024] The structural unit (I) is derived from 4-hydroxybenzoic acid (hereinafter also referred to as "HBA"). The wholly aromatic polyester of the present invention contains 35 to 75 mol% of the structural unit (I) relative to all structural units. If the content of the structural unit (I) is less than 35 mol% or exceeds 75 mol%, at least one of the vibration damping properties and the fluidity tends to be insufficient. From the viewpoint of achieving both the vibration damping properties and the fluidity, the content of the structural unit (I) is preferably 40 to 65 mol%, more preferably 44 to 55 mol%.
[0025] The structural unit (II) is derived from 6-hydroxy-2-naphthoic acid (hereinafter also referred to as "HNA"). The wholly aromatic polyester in the present invention contains 0 to 8 mol% of the structural unit (II) relative to all structural units, that is, does not contain the structural unit (II) or contains more than 0 mol% and 8 mol% or less relative to all structural units. If the content of the structural unit (II) exceeds 8 mol%, at least one of the vibration damping property and the fluidity tends to be insufficient. From the viewpoint of achieving both the vibration damping property and the fluidity, the content of the structural unit (II) is preferably 2 to 8 mol%, more preferably 2 to 6 mol%.
[0026] The structural unit (III) is derived from 1,4-phenylenedicarboxylic acid (hereinafter also referred to as "TA"). The wholly aromatic polyester in the present invention contains 4.5 to 30.5 mol% of the structural unit (III) relative to all structural units. If the content of the structural unit (III) is less than 4.5 mol% or exceeds 30.5 mol%, at least one of the vibration damping properties and the fluidity tends to be insufficient. From the viewpoint of achieving both the vibration damping properties and the fluidity, the content of the structural unit (III) is preferably 11 to 27 mol%, more preferably 16 to 24 mol%.
[0027] The structural unit (IV) is derived from 1,3-phenylenedicarboxylic acid (hereinafter also referred to as "IA"). The wholly aromatic polyester of the present invention contains 2 to 8 mol% of the structural unit (IV) relative to all structural units. If the content of the structural unit (IV) is less than 2 mol% or is 8 mol% or more, at least one of the vibration damping property and the fluidity is likely to be insufficient. From the viewpoint of achieving both the vibration damping property and the fluidity, the content of the structural unit (IV) is preferably 2 to 7 mol%, more preferably 2.5 to 5 mol%.
[0028] The structural unit (V) is derived from 4,4'-dihydroxybiphenyl (hereinafter also referred to as "BP"). The wholly aromatic polyester of the present invention contains 12.5 to 32.5 mol% of the structural unit (V) relative to all structural units. If the content of the structural unit (V) is less than 12.5 mol% or exceeds 32.5 mol%, at least one of the vibration damping properties and the fluidity tends to be insufficient. From the viewpoint of achieving both the vibration damping properties and the fluidity, the content of the structural unit (V) is preferably 17 to 30 mol%, more preferably 21 to 28 mol%.
[0029] As described above, the wholly aromatic polyester of the present invention contains specific structural units (I) to (V) in specific amounts relative to the total structural units, and therefore has particularly excellent vibration damping properties and flowability. The wholly aromatic polyester of the present invention contains the structural units (I) to (V) in a total amount of 100 mol % relative to the total structural units.
[0030] Next, the method for producing the wholly aromatic polyester of the present invention will be described. The wholly aromatic polyester of the present invention is polymerized using a direct polymerization method, an ester exchange method, etc. In the polymerization, a melt polymerization method, a solution polymerization method, a slurry polymerization method, a solid-phase polymerization method, etc., or a combination of two or more of these methods is used, and the melt polymerization method or a combination of the melt polymerization method and the solid-phase polymerization method is preferably used.
[0031] In the present invention, in the polymerization, an acylating agent for the polymerizable monomer or a monomer having an activated end as an acid chloride derivative can be used. Examples of the acylating agent include fatty acid anhydrides such as acetic anhydride.
[0032] Various catalysts can be used in these polymerizations. Representative catalysts include metal salt catalysts such as potassium acetate, magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, antimony trioxide, and tris(2,4-pentanedionato)cobalt(III), and organic compound catalysts such as 1-methylimidazole and 4-dimethylaminopyridine.
[0033] The reaction conditions are, for example, a reaction temperature of 200 to 380° C. and a final pressure of 0.1 to 760 Torr (i.e., 13 to 101,080 Pa). In particular, in the case of a melt reaction, the reaction temperature is, for example, 260 to 380° C., preferably 300 to 360° C., and the final pressure is 1 to 100 Torr (i.e., 133 to 13,300 Pa), preferably 1 to 50 Torr (i.e., 133 to 6,670 Pa).
[0034] The reaction can be started by charging all the raw material monomers (HBA, HNA, TA, IA, and BP), the acylating agent, and the catalyst into the same reaction vessel (single-stage system), or the hydroxyl groups of the raw material monomers HBA, HNA, and BP can be acylated with the acylating agent and then reacted with the carboxyl groups of TA and IA (two-stage system).
[0035] The melt polymerization is carried out by starting decompression after the reaction system has reached a predetermined temperature, and then setting the pressure at a predetermined reduced pressure. After the torque of the stirrer has reached a predetermined value, an inert gas is introduced, and the pressure is increased from a reduced pressure state to normal pressure, and then to a predetermined pressurized state, and the wholly aromatic polyester is discharged from the reaction system.
[0036] The wholly aromatic polyester produced by the above polymerization method can be further subjected to solid-phase polymerization by heating in an inert gas at normal or reduced pressure to increase the molecular weight. Preferred conditions for the solid-phase polymerization reaction are a reaction temperature of 230 to 350°C, preferably 260 to 330°C, and a final pressure of 10 to 760 Torr (i.e., 1,330 to 101,080 Pa).
[0037] Next, the properties of the wholly aromatic polyester will be described. The wholly aromatic polyester of the present invention exhibits optical anisotropy when melted. The fact that the wholly aromatic polyester of the present invention exhibits optical anisotropy when melted means that the wholly aromatic polyester of the present invention is a liquid crystalline resin.
[0038] In the present invention, the fact that the wholly aromatic polyester is a liquid crystal resin is an essential element for the wholly aromatic polyester to have both good vibration damping properties and fluidity. Some wholly aromatic polyesters composed of the above-mentioned structural units (I) to (V) do not form an anisotropic molten phase depending on the structural components and the sequence distribution in the polymer, but the liquid crystal resin in the present invention is limited to wholly aromatic polyesters that show optical anisotropy when molten.
[0039] The melt anisotropy can be confirmed by a conventional polarized light inspection method using crossed polarizers. More specifically, melt anisotropy can be confirmed by melting a sample placed on a Linkam hot stage using an Olympus polarizing microscope and observing it at a magnification of 150 times under a nitrogen atmosphere. Liquid crystal resins are optically anisotropic and transmit light when inserted between crossed polarizers. If a sample is optically anisotropic, polarized light will transmit even if it is in a molten, static liquid state, for example.
[0040] Since a nematic liquid crystal resin exhibits a significant decrease in viscosity above its melting point, the fact that it exhibits liquid crystallinity at or above its melting point is generally an indicator of processability. From the viewpoint of heat resistance, it is preferable that the melting point is as high as possible, but considering the thermal degradation during melt processing of the liquid crystal resin and the heating capacity of the molding machine, a melting point of 360°C or less is a preferable guideline. It is more preferably 300 to 360°C, and even more preferably 340 to 358°C.
[0041] The melt viscosity of the liquid crystal resin in the present invention at a temperature 10 to 20°C higher than the melting point of the liquid crystal resin and at a shear rate of 1000 / sec is preferably 500 Pa·s or less, more preferably 0.5 to 300 Pa·s, and even more preferably 1 to 100 Pa·s. When the melt viscosity is within the above range, the liquid crystal resin itself or a composition containing the liquid crystal resin is likely to have good fluidity during molding, and the filling pressure is unlikely to become excessive. In this specification, the melt viscosity is a value obtained by a measurement method in accordance with ISO 11443.
[0042] The liquid crystal resin composition according to the present invention contains the above liquid crystal resin in an amount of preferably 60 to 95% by mass, more preferably 65 to 90% by mass, and even more preferably 70 to 85% by mass, based on the entire liquid crystal resin composition. If the content of the liquid crystal resin is less than 60% by mass based on the entire liquid crystal resin composition, the vibration damping property and fluidity of the liquid crystal resin composition are likely to deteriorate, and the noise of the fan impeller obtained from the liquid crystal resin composition may increase. If the content of the liquid crystal resin is more than 95% by mass based on the entire liquid crystal resin composition, the strength and rigidity of the fan obtained from the liquid crystal resin composition may decrease.
[0043] [(B) Plate-like filler] The liquid crystalline resin composition according to the present invention can impart sufficient torsional rigidity to a fan made of the liquid crystalline resin composition by containing a predetermined amount of (B) plate-like filler having a predetermined aspect ratio. (B) The plate-like filler can be used alone or in combination of two or more kinds.
[0044] The aspect ratio of the (B) plate-like filler is 10 or more, preferably 30 or more, more preferably 50 or more. The upper limit is not particularly limited, but may be, for example, 200 or less, or 100 or less. Within the above numerical range, good torsional rigidity is easily obtained. The aspect ratio means the ratio of the average particle size (μm) to the average thickness (μm).
[0045] The average particle size of the (B) plate-like filler is preferably 1 to 500 μm, more preferably 15 to 350 μm. The average thickness is preferably 0.1 to 50 μm, more preferably 0.3 to 20 μm. Within the above numerical range, good torsional rigidity is easily obtained. In this specification, the average particle size of the (B) plate-like filler in the liquid crystal resin composition is measured by a laser diffraction / scattering particle size distribution measurement method for the particle size of the plate-like filler remaining after heating the liquid crystal resin composition at 600° C. for 2 hours to incinerate it, and the particle size at 50% of the integrated value in the volume-based particle size distribution is adopted as the average particle size of the (B) plate-like filler in the liquid crystal resin composition. In this specification, the average thickness of the (B) plate-like filler in the liquid crystal resin composition is measured by an electron microscope (SEM) observation for the thickness of the plate-like filler remaining after heating the liquid crystal resin composition at 600° C. for 2 hours to incinerate it.
[0046] Examples of the plate-like filler include glass flakes, mica, various metal foils, etc. Glass flakes and / or mica are preferred, and glass flakes are more preferred, in that the molded article obtained from the liquid crystalline resin composition has excellent torsional rigidity.
[0047] The content of the (B) plate-like filler in the liquid crystal resin composition according to the present invention is 5 to 40% by mass, preferably 5 to 30% by mass, and more preferably 15 to 30% by mass. When the content of the (B) plate-like filler is within the above range, the liquid crystal resin composition can have a sufficient fluidity, and good torsional rigidity and noise can be easily suppressed.
[0048] [(C) Fibrous filler] From the viewpoint of mechanical strength, the liquid crystal resin composition according to the present invention preferably further contains (C) a fibrous filler. The (C) fibrous filler may be used alone or in combination of two or more.
[0049] The weight average fiber length of the (C) fibrous filler is not particularly limited, and may be, for example, 200 μm or more, preferably 300 to 600 μm, and more preferably 400 to 500 μm. When the weight average fiber length is 600 μm or less, the liquid crystal resin composition is likely to have sufficient fluidity. When the weight average fiber length is 200 μm or more, the molded article obtained from the liquid crystal resin composition of the present invention is likely to have improved mechanical strength and heat resistance. In this specification, the weight average fiber length of the (C) fibrous filler in the liquid crystal resin composition is determined by taking a stereomicroscope image of the fibrous filler remaining after heating the liquid crystal resin composition at 600° C. for 2 hours to incinerate it, importing the image from a CCD camera to a PC, and measuring the fiber length of the fibrous filler by an image processing method using an image measuring device.
[0050] The average fiber diameter of the (C) fibrous filler is not particularly limited, and is, for example, 20 μm or less, preferably 5 to 15 μm. When the average fiber diameter is 20 μm or less, raising of the surface of the molded article is easily suppressed. In this specification, the average fiber diameter of the (C) fibrous filler in the liquid crystal resin composition is the average value of the fiber diameter of the fibrous filler remaining after heating the liquid crystal resin composition at 600° C. for 2 hours to incinerate it, measured by observation with an electron microscope (SEM).
[0051] Any fiber can be used as long as it satisfies the above-mentioned shape, but examples of the fibrous filler (C) include inorganic fibrous substances such as glass fiber, carbon fiber, milled fiber, asbestos fiber, silica fiber, silica-alumina fiber, zirconia fiber, boron nitride fiber, silicon nitride fiber, boron fiber, potassium titanate fiber, and further fibrous substances of metals such as stainless steel, aluminum, titanium, copper, brass, etc. In the present invention, from the viewpoint of torsional rigidity, it is preferable to use glass fiber and / or carbon fiber as component (C), and it is more preferable to use glass fiber.
[0052] The glass fiber is not particularly limited, and any known glass fiber is preferably used.The shape of the glass fiber, such as a cylinder, a cocoon shape, or an oval cross section, or the length or glass cutting method when used to manufacture chopped strands or rovings, is not particularly limited.In the present invention, the type of glass is not limited, but in terms of quality, E glass or corrosion-resistant glass having zirconium element in its composition is preferably used.
[0053] The carbon fiber is not particularly limited, and examples thereof include PAN-based carbon fiber made from polyacrylonitrile and pitch-based carbon fiber made from pitch.
[0054] The content of the fibrous filler (C) in the liquid crystal resin composition according to the present invention is preferably 5 to 20% by mass, and more preferably 5 to 15% by mass. The liquid crystal resin composition is likely to have good mechanical strength while having sufficient fluidity.
[0055] [Other ingredients] To the liquid crystal resin composition according to the present invention, other polymers, other fillers, and known substances generally added to synthetic resins, i.e., stabilizers such as antioxidants and ultraviolet absorbers, antistatic agents, flame retardants, colorants such as dyes and pigments, lubricants, release agents, crystallization accelerators, crystal nucleating agents, etc., may be appropriately added depending on the required performance, within the range not impairing the effects of the present invention. The other components may be used alone or in combination of two or more.
[0056] Examples of the other polymers include liquid crystal resins other than the (A) liquid crystal resin. However, from the viewpoint of vibration damping properties of the molded article, it is preferable that the liquid crystal resin composition according to the present invention does not contain any liquid crystal resin other than the (A) liquid crystal resin. Examples of the other polymers include epoxy group-containing copolymers. However, since gas generation due to thermal decomposition of the epoxy group-containing copolymer and swelling of molded articles such as fan impellers due to the gas generation are unlikely to occur, it is preferable that the liquid crystal resin composition according to the present invention does not contain any epoxy group-containing copolymer.
[0057] The other fillers refer to fillers other than fibrous fillers and plate-like fillers, and examples thereof include particulate fillers (eg, silica).
[0058] The method for producing the liquid crystal resin composition according to the present invention is not particularly limited as long as the components in the liquid crystal resin composition can be mixed uniformly, and can be appropriately selected from conventionally known methods for producing resin compositions. For example, a method can be mentioned in which each component is melt-kneaded and extruded using a melt-kneading device such as a single-screw or twin-screw extruder, and then the obtained liquid crystal resin composition is processed into a desired form such as powder, flakes, pellets, etc.
[0059] Since the liquid crystalline resin composition according to the present invention has excellent flowability, it can be easily molded into fan impellers and housings having thin-walled blades.
[0060] The melt viscosity of the liquid crystal resin composition measured in accordance with ISO11443 at a temperature 10 to 20°C higher than the melting point of the liquid crystal resin and a shear rate of 1000 / s is 1×105 Pa s or less (more preferably, 5 Pa s or more, 1×10 2 It is preferable that the viscosity is less than or equal to 1 Pa·s in order to ensure the fluidity of the liquid crystalline resin composition during molding of the fan impeller or housing, and to facilitate molding of the fan impeller or housing having thin blades.
[0061] <Fan> The fan according to the present invention can be obtained by molding the liquid crystalline resin composition according to the present invention, and the fan according to the present invention has excellent vibration damping properties and torsional rigidity.
[0062] The fan according to the present invention is not particularly limited, and may be a normal fan having a fan impeller having a plurality of blades and rotating to generate a flow of gas such as air, a motor for rotating the fan impeller, and a housing for accommodating the fan impeller and the motor. In addition to the fine impeller, the motor, and the housing, the fan may also have other configurations that normal fans have. In the fan according to the present invention, the configuration made of the liquid crystal resin composition according to the present invention is not particularly limited, and may be a part or all of any of the configurations, and may in particular be a part or all of the fan impeller and / or the housing, or may be the whole of the fan impeller and / or the housing.
[0063] Depending on the way the gas flows, fans can be classified into axial fans (standard axial fans, counter-rotating fans, etc.) in which the gas passes through the fan impeller in the axial direction, centrifugal fans (backward-curved fans, radial fans, multi-blade fans, etc.) in which the gas passes through the fan impeller in the radial direction, and mixed-flow fans in which the gas passes through the fan impeller at an angle to the axial direction. The fan according to the present invention is not particularly limited and may be any type of fan, but may in particular be an axial fan and / or a centrifugal fan.
[0064] Typical applications of fans include ventilation, air conditioning, and cooling of mechanical and electrical equipment. Among these, the application of the fan according to the present invention is preferably as a cooling fan for mechanical and electrical equipment, and more preferably as a cooling fan for electronic devices such as notebook PCs and servers.
[0065] Examples of the shape of the fan according to the present invention include an axial fan 1 shown in FIG. 1 and a centrifugal fan 2 shown in FIG. 2. The axial fan 1 in FIG. 1 includes a fan impeller 11, a motor for rotating the fan impeller 11, and a housing 12 for accommodating the fan impeller 11 and the motor. When the motor is driven to rotate the fan impeller 11 having a plurality of blades 111, gas passes through the fan impeller 11 in the axial direction and is blown backward. The centrifugal fan 2 in FIG. 2 includes a fan impeller 21, a motor for rotating the fan impeller 21, and a housing 22 for accommodating the fan impeller 21 and the motor. When the motor is driven to rotate the fan impeller 21 having a plurality of blades 211, gas flowing in from an intake port 23 passes through the fan impeller 21 in the radial direction and is blown to an exhaust port 24.
[0066] The thickness t of the fan impeller blade is not particularly limited, but is preferably 0.1 to 0.5 mm, more preferably 0.1 to 0.2 mm. The total length L of the fan impeller blade is not particularly limited, but is preferably 5 to 50 mm, more preferably 10 to 30 mm. The ratio L / t of the total length L of the blade to the thickness t of the blade is not particularly limited, but is preferably 50 or more, more preferably 50 to 200. When the ratio is within the above numerical range, the effect of the present invention is easily exhibited when the liquid crystal resin composition according to the present invention is used. In this specification, the thickness t of the blade means the minimum thickness, and the total length L of the blade means the length of the straight line connecting the base and tip of the blade in the radial direction.
[0067] The diameter of the fan impeller is not particularly limited, but is preferably 10 to 100 mm, more preferably 20 to 60 mm. The number of blades of the fan impeller is not particularly limited, but is preferably 30 to 80, more preferably 40 to 60. Within the above numerical ranges, the effects of the present invention are easily exhibited when the liquid crystalline resin composition according to the present invention is used. EXAMPLES
[0068] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these.
[0069] <Examples 1 to 5 and Comparative Examples 1 to 5> In the following Examples and Comparative Examples, liquid crystal resins LCP1 to LCP4 were produced as follows, in which the melting point and melt viscosity of the pellets were measured under the following conditions.
[0070] [Melt point measurement] Using a TA Instruments DSC, the liquid crystal resin was measured at a temperature increase rate of 20°C / min from room temperature to observe the endothermic peak temperature (Tm1), and then the resin was held at a temperature of (Tm1+40)°C for 2 minutes. The resin was then cooled to room temperature at a temperature decrease rate of 20°C / min, and the endothermic peak temperature was measured again at a temperature increase rate of 20°C / min.
[0071] [Melt viscosity measurement] The melt viscosity of the liquid crystal resin was measured in accordance with ISO 11443 using a Capillograph 1B model manufactured by Toyo Seiki Seisakusho Co., Ltd. at a temperature 10 to 20°C higher than the melting point of the liquid crystal resin, using an orifice with an inner diameter of 1 mm and a length of 20 mm, and at a shear rate of 1000 / sec. The measurement temperatures were 380°C for LCP1, 350°C for LCP2, 300°C for LCP3, and 340°C for LCP4.
[0072] (LCP1 manufacturing method) A polymerization vessel equipped with a stirrer, a reflux column, a monomer inlet, a nitrogen inlet, and a pressure reduction / outlet line was charged with the following raw material monomers, a fatty acid metal salt catalyst, and an acylating agent, and nitrogen replacement was started. (I) 4-Hydroxybenzoic acid: 1040 g (48 mol%) (HBA) (II) 6-hydroxy-2-naphthoic acid: 89 g (3 mol%) (HNA) (III) Terephthalic acid: 547 g (21 mol%) (TA) (IV) Isophthalic acid: 91 g (3.5 mol%) (IA) (V) 4,4'-dihydroxybiphenyl: 716g (24.5 mol%) (BP) Potassium acetate catalyst: 110mg Acetic anhydride: 1644g After the raw materials were charged into the polymerization vessel, the temperature of the reaction system was raised to 140°C and the reaction was carried out at 140°C for 1 hour. The temperature was then raised further to 360°C over 5.5 hours, and the pressure was then reduced to 5 Torr (i.e., 667 Pa) over 20 minutes, and melt polymerization was carried out while distilling off acetic acid, excess acetic anhydride, and other low boiling points. After the stirring torque reached a specified value, nitrogen was introduced to change the pressure from reduced pressure to normal pressure and then to pressurized state, the polymer was discharged from the bottom of the polymerization vessel, and the strands were pelletized. The melting point of the obtained pellets was 355°C and the melt viscosity was 10 Pa·s.
[0073] (LCP2 manufacturing method) A polymerization vessel equipped with a stirrer, a reflux column, a monomer inlet, a nitrogen inlet, and a pressure reduction / outlet line was charged with the following raw material monomers, a fatty acid metal salt catalyst, and an acylating agent, and nitrogen replacement was started. (I) 1,380 g (60 mol%) of 4-hydroxybenzoic acid (HBA) (II) 157 g (5 mol%) of 6-hydroxy-2-naphthoic acid (HNA) (III) Terephthalic acid 484 g (17.5 mol%) (TA) (V) 4,4'-dihydroxybiphenyl 388g (12.5 mol%) (BP) (VI) 126 g (5 mol%) of N-acetyl-p-aminophenol (APAP) Potassium acetate catalyst 110mg Acetic anhydride 1659g After the raw materials were charged into the polymerization vessel, the temperature of the reaction system was raised to 140°C and the reaction was carried out at 140°C for 1 hour. The temperature was then raised further to 340°C over 4.5 hours, and the pressure was then reduced to 10 Torr (i.e., 1330 Pa) over 15 minutes, and melt polymerization was carried out while distilling off acetic acid, excess acetic anhydride, and other low boiling points. After the stirring torque reached a predetermined value, nitrogen was introduced to change the pressure from reduced pressure to normal pressure and then to pressurized state, the polymer was discharged from the bottom of the polymerization vessel, and the strands were pelletized. The melting point of the obtained pellets was 336°C and the melt viscosity was 20 Pa·s.
[0074] (LCP3 manufacturing method) A polymerization vessel equipped with a stirrer, a reflux column, a monomer inlet, a nitrogen inlet, and a pressure reduction / outlet line was charged with the following raw material monomers, a fatty acid metal salt catalyst, and an acylating agent, and nitrogen replacement was started. (I) 4-Hydroxybenzoic acid: 1660 g (73 mol%) (HBA) (II) 6-hydroxy-2-naphthoic acid: 837 g (27 mol%) (HNA) Potassium acetate catalyst: 165mg Acetic anhydride: 1714g After the raw materials were charged into the polymerization vessel, the temperature of the reaction system was raised to 140°C and the reaction was carried out at 140°C for 1 hour. The temperature was then raised further to 325°C over 3.5 hours, and the pressure was then reduced to 5 Torr (i.e., 667 Pa) over 20 minutes, and melt polymerization was carried out while distilling off acetic acid, excess acetic anhydride, and other low boiling points. After the stirring torque reached a predetermined value, nitrogen was introduced to change the pressure from reduced pressure to normal pressure and then to pressurized state, the polymer was discharged from the bottom of the polymerization vessel, and the strands were pelletized. The melting point of the obtained pellets was 280°C and the melt viscosity was 44.0 Pa·s.
[0075] (LCP4 manufacturing method) A polymerization vessel equipped with a stirrer, a reflux column, a monomer inlet, a nitrogen inlet, and a pressure reduction / outlet line was charged with the following raw material monomers, a fatty acid metal salt catalyst, and an acylating agent, and nitrogen replacement was started. (I) 4-hydroxybenzoic acid: 1,347 g (60 mol%) (HBA) (III) Terephthalic acid: 378 g (14 mol%) (TA) (IV) Isophthalic acid: 162 g (6 mol%) (IA) (V) 4,4'-dihydroxybiphenyl: 605 g (20 mol%) (BP) Potassium acetate catalyst: 110mg Acetic anhydride: 1704g After the raw materials were charged into the polymerization vessel, the temperature of the reaction system was raised to 140°C and the reaction was carried out at 140°C for 3 hours. The temperature was then raised further to 360°C over 4.5 hours, and the pressure was then reduced to 10 Torr (i.e., 1330 Pa) over 15 minutes, and melt polymerization was carried out while distilling off acetic acid, excess acetic anhydride, and other low boiling points. After the stirring torque reached a specified value, nitrogen was introduced to change the state from reduced pressure to normal pressure and then to pressurized state, the polymer was discharged from the bottom of the polymerization vessel, and the strands were pelletized. The melting point of the obtained pellets was 320°C and the melt viscosity was 20 Pa·s.
[0076] (Components other than liquid crystal resin) Glass flakes: REFG-108 manufactured by Nippon Sheet Glass Co., Ltd. (average particle size: 600 μm, aspect ratio: 120) Mica: AB-25S manufactured by Yamaguchi Mica Co., Ltd. (average particle size: 23 μm, aspect ratio: 40 to 50) Talc: Crown Talc PP manufactured by Matsumura Sangyo Co., Ltd. (average particle size: 13 μm, aspect ratio: 8) Glass fiber: ECS03T-786H manufactured by Nippon Electric Glass Co., Ltd., chopped strands with an average fiber diameter of 10 μm and an average fiber length of 3 mm
[0077] Each of the liquid crystal resins obtained above and the components other than the liquid crystal resins described above were mixed using a twin screw extruder to obtain a liquid crystal resin composition. The blending amount of each component is as shown in Table 1. In the following, "%" regarding the blending amount in the table indicates mass %. The extrusion conditions for obtaining the liquid crystal resin composition are as follows. As a result of measurement by the measurement method described in this specification, the average particle size of the glass flakes in the obtained liquid crystal resin composition was 350 μm and the aspect ratio was 70. The average particle size of the mica was 23 μm, the aspect ratio was 40 to 50, the average particle size of the talc was 13 μm, the aspect ratio was 8, the average fiber diameter of the glass fibers was 10 μm, and the weight average fiber length was 450 μm. [Extrusion conditions] The temperature of the cylinder installed at the main feed port was set to 250°C, and the temperatures of the other cylinders were all as follows. All the liquid crystal resins were fed from the main feed port. The fillers were fed from the side feed port. Other cylinder temperatures: 370°C (Examples 1 to 4 and Comparative Examples 1 to 3) 340°C (Example 5) 350°C (Comparative Example 4) 300°C (Comparative Example 5)
[0078] (Measurement of Melt Viscosity of Liquid Crystalline Resin Composition) The melt viscosity of the liquid crystal resin composition was measured in accordance with ISO11443 using a Capillograph 1B model manufactured by Toyo Seiki Seisakusho Co., Ltd. at a temperature 10 to 20°C higher than the melting point of the liquid crystal resin, using an orifice with an inner diameter of 1 mm and a length of 20 mm, and at a shear rate of 1000 / sec. The measurement temperatures were 380°C for the liquid crystal resin composition using LCP1, 350°C for the liquid crystal resin composition using LCP2, 300°C for the liquid crystal resin composition using LCP3, and 340°C for the liquid crystal resin composition using LCP4. The results are shown in Table 1.
[0079] (Thin wall bending strength) The liquid crystal resin composition was injection molded under the following molding conditions to obtain a test piece of 30 mm x 30 mm x 0.3 mm. The center part of this test piece was cut out in the flow direction and in the direction perpendicular to the flow to obtain a test piece for measurement (30 mm x 5 mm x 0.3 mm). The bending strength in the flow direction and the direction perpendicular to the flow was measured using this test piece for measurement. The results are shown in Table 1. [Molding conditions] Molding machine: Sumitomo Heavy Industries, Ltd., SE100DU Cylinder Temperature: 370°C (Examples 1 to 4 and Comparative Examples 1 to 3) 340°C (Example 5) 350°C (Comparative Example 4) 300°C (Comparative Example 5) Mold temperature: 90℃ Injection speed: 33mm / sec
[0080] (Loss factor (vibration damping characteristics)) The liquid crystal resin composition was injection molded under the following molding conditions to obtain a test piece of 200 mm x 10 mm x 1.6 mm. The test piece was then attached to an accelerator "512-D" manufactured by EMIC Co., Ltd. so that the center was supported, and the loss factor (vibration damping property) was measured at a temperature of 23°C and a frequency of 10,000 Hz by the half-value width method in accordance with JIS G0602. The results are shown in Table 1. [Molding conditions] Molding machine: Sumitomo Heavy Industries, Ltd., SE100DU Cylinder Temperature: 370°C (Examples 1 to 4 and Comparative Examples 1 to 3) 340°C (Example 5) 350°C (Comparative Example 4) 300°C (Comparative Example 5) Mold temperature: 90℃ Injection speed: 33mm / sec
[0081] (Thin wall fluidity) A rod-shaped product with a width of 5 mm and a thickness of 0.2 mm was molded under the following molding conditions, and the flow distance was measured. The average value of five tests was taken as the flow distance. The results are shown in Table 1. [Molding conditions] Molding machine: Sumitomo Heavy Industries, Ltd., SE30DUZ Cylinder Temperature: 370°C (Examples 1 to 4 and Comparative Examples 1 to 3) 340°C (Example 5) 350°C (Comparative Example 4) 300°C (Comparative Example 5) Mold temperature: 80℃ Injection speed: 300mm / sec Injection pressure: 100MPa
[0082] The liquid crystalline resin composition was injection molded under the following molding conditions to obtain a centrifugal fan impeller (blade thickness t: 0.2 mm, blade total length L: 15 mm, blade number: 45, fan impeller diameter: 46 mm) as shown in FIG. [Molding conditions] Molding machine: Sumitomo Heavy Industries, Ltd., SE100DU Cylinder Temperature: 370°C (Examples 1 to 4 and Comparative Examples 1 to 3) 340°C (Example 5) 350°C (Comparative Example 4) 300°C (Comparative Example 5) Mold temperature: 90℃ Injection speed: 33mm / sec
[0083] (Blade vertical load (torsional rigidity)) A load P was applied to the fan impeller obtained above using a mechanical force gauge (UKT-2K, manufactured by Imada Co., Ltd.) in the direction shown in Figure 4 until the blade broke. The maximum load during this period was measured as the blade vertical load (torsional rigidity). The results are shown in Table 1.
[0084] (Noise suppression) The centrifugal fan equipped with the fan impeller obtained above was installed inside a notebook computer, and noise was measured in an anechoic box under the following conditions using a precision sound level meter ("NA-60" manufactured by Rion Co., Ltd.) and an FFT analyzer ("CF5220" manufactured by Ono Sokki Co., Ltd.). The results are shown in Table 1. Revolution speed: 15,000 rpm Measurement distance: 100mm (above the axis center) Rotation direction: forward rotation
[0085] [Table 1]
[0086] As shown in Table 1, in the examples, the vibration damping characteristics, the blade normal load, and the noise suppression were all evaluated as being good. Therefore, it was confirmed that the liquid crystal resin composition according to the present invention is excellent in vibration damping characteristics and torsional rigidity, and that the fan obtained from this liquid crystal resin composition is excellent in vibration damping characteristics and torsional rigidity, and noise is suppressed. Therefore, the liquid crystal resin composition can be suitably used for manufacturing fans.
Claims
1. A liquid crystalline resin composition for a fan, comprising: (A) a liquid crystalline resin; and (B) a plate-like filler, The (A) liquid crystalline resin contains the following structural units (I), (III), (IV) and (V), and may or may not contain the following structural unit (II), The content of the structural unit (I) is 35 to 75 mol % based on all structural units, The content of the structural unit (II) is 0 to 8 mol% based on all structural units, The content of the structural unit (III) is 4.5 to 30.5 mol% relative to all structural units, The content of the structural unit (IV) is 2 to 8 mol% based on all structural units; The content of the structural unit (V) relative to all structural units is 12.5 to 32.5 mol %, a wholly aromatic polyester which exhibits optical anisotropy when melted, in which the total content of the structural units (I) to (V) is 100 mol % based on all structural units; The plate-like filler (B) has an aspect ratio, which is the ratio of the average particle diameter (μm) to the average thickness (μm), of 30 to 200, The content of the plate-like filler (B) is 5 to 40% by mass based on the entire liquid crystal resin composition, A liquid crystalline resin composition having a loss factor of 0.05 or more at a temperature of 23° C. and a frequency of 10,000 Hz, as measured in accordance with JIS G0602. 【Chemistry 1】
2. The liquid crystal resin (A) is composed of structural units (I), (II), (III), (IV) and (V), The content of the structural unit (I) is 35 to 75 mol % based on all structural units, The content of the structural unit (II) is 2 to 8 mol% based on all structural units, The content of the structural unit (III) is 4.5 to 30.5 mol% relative to all structural units, The content of the structural unit (IV) is 2 to 8 mol% based on all structural units; The content of the structural unit (V) relative to all structural units is 12.5 to 32.5 mol %, a wholly aromatic polyester which exhibits optical anisotropy when melted, in which the total content of the structural units (I) to (V) is 100 mol % based on all structural units; The liquid crystal resin composition according to claim 1 , wherein the plate-like filler (B) is glass flakes.
3. The liquid crystal resin composition according to claim 1 or 2, further comprising (C) a fibrous filler.
4. 4. The liquid crystalline resin composition according to claim 3, wherein the content of the fibrous filler (C) is 5 to 20% by mass based on the entire liquid crystalline resin composition.
5. 5. The liquid crystal resin composition according to claim 3, wherein the fibrous filler (C) is a glass fiber and / or a carbon fiber.
6. A fan comprising the liquid crystal resin composition according to any one of claims 1 to 5.
Citation Information
Patent Citations
Vibration-damping liquid crystalline resin composition and molded product composed of the same composition
JP2001064498A
Axial fan equipment and heating element cooling device
JP2005039253A
Production method of molded article and composite resin composition
JP2016124947A
Liquid crystal polyester resin pellet, method for manufacturing the same, and method for manufacturing molded article
JP2021028373A
JPP6741834B